2017
DOI: 10.1515/cclm-2016-0792
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of glycated hemoglobin among patients with ST-segment elevation myocardial infarction: a systematic review and meta-analysis

Abstract: Abstract:Many studies have shown the prognostic significance of glycated hemoglobin (HbA 1c ) for overall coronary artery disease (CAD). But less is known about the role that HbA 1c played in the prognosis of patients diagnosed with ST-segment elevation myocardial infarction (STEMI).Results from previous studies were controversial. Therefore, a meta-analysis was conducted to investigate whether admission HbA 1c level was a predictor of short-and longterm mortality rates among patients diagnosed with STEMI. Rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
1
2
1
Order By: Relevance
“…As for all the CAD populations, higher HbA1c led to an increased probability of MACE and composite endpoint events (HR for MACE and composite events: 1.97, 1.67) . This was consistent with the conclusions of many previous studies ( 23 , 26 , 37 , 38 ). What's more, when combined with clinical depression, the prognosis got even worse (HR for MACE and composite events: 2.9, 2.12) .…”
Section: Discussionsupporting
confidence: 94%
“…As for all the CAD populations, higher HbA1c led to an increased probability of MACE and composite endpoint events (HR for MACE and composite events: 1.97, 1.67) . This was consistent with the conclusions of many previous studies ( 23 , 26 , 37 , 38 ). What's more, when combined with clinical depression, the prognosis got even worse (HR for MACE and composite events: 2.9, 2.12) .…”
Section: Discussionsupporting
confidence: 94%
“…Although the present study suggested that HbA1c may not be related to extent of infarct, in recent meta-analysis elevated HbA1c was associated with increased short-term mortality in ACS patients without DM history and without DM (17). In another meta-analysis elevated HbA1c level among STEMI patients was an indicator of 1.25-fold 30day mortality risk and 1.45-fold long-term mortality risk, respectively (19). Individuals with undiagnosed DM are at high risk of developing diabetic complications, including cardiovascular disease (20).…”
Section: Discussioncontrasting
confidence: 69%
“…To our knowledge, this is the first systematic review regarding the predictive value of HbA1c for short-term mortality in ACS patients. Although there is a similar review regarding STEMI patients [57], it did not explain the heterogeneity explicitly. As unstable angina and NSTEMI share the same pathological process as STEMI, we took all the ACS patients into account in this systematic review.…”
Section: Discussionmentioning
confidence: 99%